2019
DOI: 10.1021/jacs.9b00950
|View full text |Cite
|
Sign up to set email alerts
|

Triptycene Tripods for the Formation of Highly Uniform and Densely Packed Self-Assembled Monolayers with Controlled Molecular Orientation

Abstract: When employing self-assembled monolayers (SAMs) for tuning surface and interface properties, organic molecules that enable strong binding to the substrate, large-area structural uniformity, precise alignment of functional groups, and control of their density are highly desirable. To achieve these goals, tripod systems bearing multiple bonding sites have been developed as an alternative to conventional monodentate systems. Bonding of all three sites has, however, hardly been achieved, with the consequence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
131
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(136 citation statements)
references
References 77 publications
4
131
0
1
Order By: Relevance
“…−1 eV) . The adsorption energies of triptycene tripods with three thiol anchors, which account for loss of hydrogen upon binding to a gold surface, were found to be −1.62 eV (for less flexible aryl thiols) and −2.67 eV (for more flexible benzylic thiols) . The tetrapodal anchors perform comparably to the former case despite using thiomethyl anchors rather than thiols.…”
Section: Resultsmentioning
confidence: 93%
“…−1 eV) . The adsorption energies of triptycene tripods with three thiol anchors, which account for loss of hydrogen upon binding to a gold surface, were found to be −1.62 eV (for less flexible aryl thiols) and −2.67 eV (for more flexible benzylic thiols) . The tetrapodal anchors perform comparably to the former case despite using thiomethyl anchors rather than thiols.…”
Section: Resultsmentioning
confidence: 93%
“…For instance, Reinhoudt have probed this issue of SAMs of β‐cyclodextrin heptathioether derivatives by XPS analysis and found that on average only 4.5 of the 7 attachment points were used . In order to have an ideal homogenous immobilization, the use of a flexible methylene linker between the rigid framework and the contact site would be helpful in some cases …”
Section: Discussionmentioning
confidence: 99%
“…Very recently,F ukushima and co-workersr eported the interfacial assembly of 1,8,13-trimercaptomethyltriptycene (8)a nd 1,8,13-trimercaptotriptycene (9)o nA u(111)s urface ( Figure 4). [62] In comparison, the monolayers of 9 exhibits al ow degree of order and noticeable deviation from the desired tripodal anchoring; however,t he assembly of 8 results in an almostu pright orientation of the benzene rings and large-area structural uniformity through ap erfect three-point contact. This difference is ascribed to the effect of the flexible methylene linkerso f8.…”
Section: Tripodal Anchorsmentioning
confidence: 98%
See 2 more Smart Citations